Concanavalin A-targeted mesoporous silica nanoparticles for infection treatment. (15th September 2019) - Martínez-Carmona, Marina; Izquierdo-Barba, Isabel; Colilla, Montserrat; Vallet-Regí, María
Graphical abstract: Abstract: The ability of bacteria to form biofilms hinders any conventional treatment for chronic infections and has serious socio-economic implications. For this purpose, a nanocarrier capable of overcoming the barrier of the mucopolysaccharide matrix of the biofilm and releasing its loaded-antibiotic within this matrix would be desirable. Herein, we developed a new nanosystem based on levofloxacin (LEVO)-loaded mesoporous silica nanoparticles (MSN) decorated with the lectin concanavalin A (ConA). The presence of ConA promotes the internalization of this nanosystem into the biofilm matrix, which increases the antimicrobial efficacy of the antibiotic hosted within the mesopores. This nanodevice is envisioned as a promising alternative to conventional treatments for infection by improving the antimicrobial efficacy and reducing side effects. Statement of Significance: The present study is focused on finding an adequate therapeutic solution for the treatment of bone infection using nanocarriers that are capable of overcoming the biofilm barrier by increasing the therapeutic efficacy of the loaded antibiotic. For this purpose, we present a nanoantibiotic that increases the effectiveness of levofloxacin to destroy the biofilm formed by the model bacterium E. coli. This work opens new lines of research in the treatment of chronic infections based on nanomedicines.